Seismicity Study of Khanaqin Area - Abd Alridha, Nawal; Jasim Mohammed, Hassanain (Iraqi Journal of Science, 2023)
A seismicity study of khanaqin city and surrounding area is carried out. More than 270quakes between 22 Nov. to 30 Dec. 2013 are recorded by Iraqi Seismic Network (ISN).Analyses of these events show earthquakes magnitude range between (1.2 – 5.6) degree,focal depth between (4 – 27) km. Seismotectonic map for studied area is drawn .Isointensity maps for the felt earthquakes are drawn and show the intensity rangebetween (I-VII) according to the modified Mercalli scale. Fault plane solutions for fourevents in the study area indicate a reverse strike slip solution along planes with NW –SEdirection